La guerra di Successione spagnola: l’Italia, l’Europa, il mondo (1700-1714) (Quaderni del Corso di laurea in Filosofia, 2024)
The War of the Spanish Succession is a periodizing moment in European history. The present volume, with its insights into the realities of Milan, Naples, Sicily and Sardinia, seeks to explore the reactions of the local aristocracies before the outbreak of the conflict and to bring out how this moment of detachment from the Spanish Monarchy, of which these dominions had been a part for centuries, was transformed into a phase of political and institutional maturation that would continue in the following decades.